1998
DOI: 10.1128/aac.42.5.1151
|View full text |Cite
|
Sign up to set email alerts
|

Defluorinated Sparfloxacin as a New Photoproduct Identified by Liquid Chromatography Coupled with UV Detection and Tandem Mass Spectrometry

Abstract: Photodegradation of sparfloxacin was observed by means of high-pressure liquid chromatography with UV detection and liquid chromatography coupled with UV detection and tandem mass spectrometry (LC-MS/MS). Three products were detected. Comparison with an independently synthesized derivative of sparfloxacin revealed the structure of one product which is believed to be 8-desfluorosparfloxacin. The second product is likely to be formed by the splitting off of a fluorine and a cyclopropyl ring. Thus, photodefluorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Forced degradation studies of CLI which was exposed to sunlight for 2 h reveal two mechanisms of photodegradation: loss of a chlorine atom at position 8 followed by reactions involving the fluoroquinolone nucleus, and degradation of the pyrrolidine side chain [75]. Photodegradation of SPA was observed after irradiation with UV light for 8 h, yielding a photoproduct that is likely to have lost the fluorine atom at position 8 and another involving the loss of that fluorine atom and the cyclopropyl group at position 1; no photodegradation of the piperazine side chain was observed [74]. SIT decompose rapidly in aqueous solution by photoirradiation with a fluorescent lamp (that emits visible and UV light).…”
Section: Physicochemical Properties and Stability Of Fluoroquinolonesmentioning
confidence: 87%
See 2 more Smart Citations
“…Forced degradation studies of CLI which was exposed to sunlight for 2 h reveal two mechanisms of photodegradation: loss of a chlorine atom at position 8 followed by reactions involving the fluoroquinolone nucleus, and degradation of the pyrrolidine side chain [75]. Photodegradation of SPA was observed after irradiation with UV light for 8 h, yielding a photoproduct that is likely to have lost the fluorine atom at position 8 and another involving the loss of that fluorine atom and the cyclopropyl group at position 1; no photodegradation of the piperazine side chain was observed [74]. SIT decompose rapidly in aqueous solution by photoirradiation with a fluorescent lamp (that emits visible and UV light).…”
Section: Physicochemical Properties and Stability Of Fluoroquinolonesmentioning
confidence: 87%
“…It is suggested that light irradiation generates toxic photoproducts intermediates (e.g. carbenes) and reactive oxygen species that may attack cell components and cause tissue damage, leading to remarkable phototoxicity of fluoroquinolones [47,74,75,77,78]. An increased incidence of phototoxicity was observed in dihalogenated fluoroquinolones and also in molecules that contain a methoxy group at position 5 and molecules with a cyclopropyl or ethyl group at position 1 [39].…”
Section: Physicochemical Properties and Stability Of Fluoroquinolonesmentioning
confidence: 98%
See 1 more Smart Citation
“…B). Modifications in these groups have also been described in the literature (Engler et al ., ; Fasani et al ., ; Lovdahl and Priebe, Hubicka et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…A key point of the action spectrum obtained in the present study is the extension to visible range beyond the absorption wavelengths. It has been shown that at least three photoproducts are generated by irradiation of SPFX with UV light from a high-pressure Hg discharge lamp (17). Although their absorption characteristics are not known, it is likely that the photoproducts are involved in the extension of the action spectrum, given that they absorb light at longer wavelengths than SPFX and form single-strand breaks.…”
Section: Discussionmentioning
confidence: 99%